Causa da resistência de Lipaphis pseudobrassicae (DAVIS, 1914) ao parasitoide Diaeretiella rapae (McINTOSH, 1855) e sua influência sobre o parasitismo de Myzus persicae (SULZER, 1776) - Ferreira, Samira Evangelista (2013)
The aphid Lipaphis pseudobrassicae (Davis, 1914) (Hemiptera: Aphididade) is an important pest of Brassicaceae plants. In Uberlândia, Minas Gerais, this aphid has low percentages of parasitism because of its resistance to the parasitoid Diaeretiella rapae (McIntosh) and the cause of resistance is unknown. Variations in susceptibility or resistance to natural enemies can impact in different ways on the interaction of herbivore populations. The aims of this study was to determine if the resistance of L. pseudobrassicae is caused by individual biotype or by association with secondary endosymbionts organisms and verify if the parasitism of M. persicae is changed in the presence of resistant L. pseudobrassicae. In laboratory we identified clones resistant and susceptible to parasitoid, verified the influence of superparasitism in the resistance, the loss of resistance in the aphid s progeny, the presence of encapsulation structures of the parasitoid in parasitized aphids and molecular tests to compare the composition of symbionts in resistant and susceptible clones were made. The interaction experiment was conducted on green collard plants, covered with fine net cages (anti aphid net) in green house (average temperature of 28ºC). Each plant was infested with 30 M. persicae and 30 L. pseudobrassicae resistant or susceptible to the parasitoid D. rapae and two female parasitoids were released. In laboratory the parasitism in susceptible clones ranged from 47 to 67% and in resistant clone was zero. Superparasitism did not alter the resistance, however, aphids resistant that received three ovipositions had a higher proportion of individuals with changes caused by parasitism than those who received one oviposition of D. rapae. It was verified the loss of the resistance in 6.7% of the progeny of the resistant clone. There were no structures that indicate the encapsulation of parasitoid eggs or larvae of parasitoid in resistant aphids. Molecular tests indicated no difference in the composition of symbiotic bacteria between resistant and susceptible aphids of the same clone. In the green house experiment the number of mummified aphids was lower in the population of L. pseudobrassicae resistant than susceptible to the parasitoid. It was observed that the number of resistant L. pseudobrassicae alive was higher than the number of M. persicae. We also observed a lower percentage of parasitism in the L. pseudobrassicae resistant to the parasitoid, but there was no influence of the L. pseudobrassicae resistant in M. persicae population or parasitism. The results indicate that the cause of L. pseudobrassicae s resistance to the parasitoid D. rapae is due to the presence of secondary endosymbionts and shows that D. rapae can be used to control M. persicae even when it is associated with a population of L. pseudobrassicae resistant to the parasitoid.